The Implementation of the Educaplay Interactive Digital Media Application via the Problem-Based Learning Model to Improve Learning Outcomes in Mathematics (Whole Number Multiplication) for Grade III Students - Ayatullah Jaya Kusuma; Ribut Prastiwi Sriwijayanti; Didit Yulian Kasdriyanto (International Journal of Educational Evaluation and Policy Analysis, 2026)
This study examines the academic performance and motivation of third-grade students at SDN Ban-jarsawah 2 with respect to their comprehension of abstract mathematical concepts, particularly whole numbers, as demonstrated by the considerable proportion of students who do not meet the Minimum Mastery Criteria (KKM) score of 75. The predominance of traditional teaching approaches and a lack of diversity in educational methods are the causes of this predicament. The study is to analyse student learning results and explain the use of the Problem Based Learning (PBL) paradigm, which is supported by the interactive digital media application Edu-caplay. Two phases of a Classroom Action Research (CAR) methodology were used, each of which included preparation, execution, reflection, and observation. The research subjects were fifteen third-graders from SDN Banjarsawah 2. Data collection techniques included observation, learning achievement tests, and recording; data analysis techniques included both qualitative and quantitative descriptive approaches. The results showed that relatively few students met the learning requirements in the initial condition (pre-intervention), indicating low student learning achievement. After the intervention was implemented in Cycle I, the class-wide learning attainment rate reached 60% (9 out of 15 students), and the teacher activity implementation rate was 62.5% (rated "Fair"). In Cycle II, student learning results significantly increased following reflection and approach modification.